Increased frequency of CD4+CD25highCD127low T cells early after lung transplant is associated with improved graft survival – a retrospective study. (31st January 2020) - Ius, Fabio; Salman, Jawad; Knoefel, Ann‐Kathrin; Sommer, Wiebke; Nakagiri, Tomoyuki; Verboom, Murielle; Siemeni, Thierry; Poyanmehr, Reza; Bobylev, Dmitry; Kuehn, Christian; Avsar, Murat; Erdfelder, Caroline; et al.
Summary: In this retrospective study, we analyzed the presence of any association of three CD4 + CD25 high regulatory T‐cell subpopulations at 3 weeks after lung transplantation with the later incidence of chronic lung allograft dysfunction and graft survival. Among lung‐transplanted patients between January 2009 and April 2018, only patients with sufficient T‐cell measurements at 3 weeks after transplantation were included into the study. Putative regulatory T cells were defined as CD4 + CD25 high T cells, detected in peripheral blood and further analyzed for CD127 low, FoxP3 +, and CD152 + using fluorescence‐activated cell sorting (FACS) analysis. Associations of regulatory T cells with chronic lung allograft dysfunction (CLAD) and graft survival were evaluated using Cox analysis. During the study period, 724 (71%) patients were included into the study. Freedom from chronic lung allograft dysfunction (CLAD) and graft survival amounted to 66% and 68% at 5 years. At the multivariable analysis, increasing frequencies of CD127 low were associated with better freedom from CLAD (hazard ratio for each 1% increase of %CD127 low, HR = 0.989, 95% CI = 0.981–0.996, P = 0.003) and better graft survival (HR = 0.991, 95% CI = 0.984–0.999, P = 0.026). A higher frequency of CD127 low regulatory T cells in peripheral blood early after lung transplantation estimated a protective effect against chronic lung allograft dysfunction, mortality, and re‐transplantation.